Evidence of horizontal transmission of Wolbachia wCcep in rice moths parasitized by Trichogramma chilonis and its persistence across generations - Lai, C. T.; Hsiao, Y. T.; Wu, Li-Hsin (Frontiers in Insect Science, 2024)
The horizontal transmission of endosymbionts between hosts and parasitoids plays a crucial role in biological control, yet its mechanisms remain poorly understood. This study investigates the dynamics of horizontal transfer of Wolbachia (wCcep) from the rice moth, Corcyra cephalonica, to its parasitoid, Trichogramma chilonis. Through PCR detection and phylogenetic analysis, we demonstrated the presence of identical wCcep strains in both host and parasitoid populations, providing evidence for natural horizontal transmission. To investigate thoroughly, Wolbachia-free colonies were acquired through tetracycline treatment, and the initial density of wCcep in host eggs significantly influences transmission efficiency. High-density wCcep infections led to rapid transmission, with F1 parasitoid titers increasing by as much as 100-fold, while low-density infections exhibited more gradual increases. Additionally, without continuous exposure to infected hosts, wCcep density in T. chilonis diminished over generations. These findings enhance our understanding of Wolbachia’s transfer dynamics and have important implications for developing effective and sustainable biological control strategies using parasitoid wasps, particularly in managing Wolbachia-related pest populations in agricultural systems.